2016
DOI: 10.1007/s11019-016-9712-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences that matter: developing critical insights into discourses of patient-centeredness

Abstract: Patient-centeredness can be considered a popular, and at the same time “fuzzy”, concept. Scientists have proposed different definitions and models. The present article studies scientific publications that discuss the meaning of patient-centeredness to identify different “discourses” of patient-centeredness. Three discourses are presented; the first is labelled as “caring for patients”, the second as “empowering patients” and the third as “being responsive”. Each of these discourses has different things to say … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 55 publications
0
61
0
6
Order By: Relevance
“…Insights from the sociological, political science and public administration literature show that on both levels, participation practice is far more complex than policy documents often suggest. This raises important questions for health‐care professionals and policymakers alike . We want to build on the critical literature by focusing on one aspect of participation on the individual level: self‐management.…”
Section: Introductionmentioning
confidence: 99%
“…Insights from the sociological, political science and public administration literature show that on both levels, participation practice is far more complex than policy documents often suggest. This raises important questions for health‐care professionals and policymakers alike . We want to build on the critical literature by focusing on one aspect of participation on the individual level: self‐management.…”
Section: Introductionmentioning
confidence: 99%
“…First, the initial concept of (patient) centredness arose from the practice and research domains of medicine in an attempt to shift from approaching the person as the passive target of medical intervention to a model where the person is actively involved in care and decision‐making processes. It was felt that improving communication between the physician and the person, empowering the individual in their care and decision‐making, and sharing responsibility and power within the relationship would result in improved health outcomes (Duggan et al., ; Hughes et al., ; Leplege et al., ; Pluut, ). Second, social science research revealed a need for sociocultural change in healthcare fostering inclusion, open communication, and individual autonomy and choice over provider‐directed care (Hughes et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Such critiques have also been aimed at measures that attempt to pin down and operationalize concepts so they can be "ticked off" an assessment checklist often by oversimplifying PCC [5,8,9]. Both Dewing and McCormack [8] and Pluut [10] have recently argued that the impetus to create a single standard definition of PCC has resulted in a proliferation of PCC models with little value added. Despite these problems, the multiplicity of available models also provides a richness for fleshing out the complexities of PCC and its applications.…”
Section: Introductionmentioning
confidence: 99%